Strategi Komunikasi BNNK Tapanuli Selatan Dalam Pencegahan, Pemberantasan, Penyalahgunaan Dan Peredaran Gelap Narkoba (P4GN) - Mhd. Latip kahpi (IAIN Padangsidimpuan, 2022)
Abstract South Tapanuli BNNK as a vertical agency representing BNN in the South Tapanuli jurisdiction has tried to take concrete actions in dealing with this drug disaster, although with various limitations it has not been able to cover the wider community of South Tapanuli to socialize the dangers of drugs in order to prevent drug abuse which is increasingly concerning. . The purpose of this study was to identify and analyze the Communication Strategy of the South Tapanuli BNNK in the Prevention, Eradication, and Drug Abuse (P4GN). This type of research is field research (Field Research). By using descriptive research methods, with qualitative data types. Descriptive research is research contained in the research problem. The representation is done by describing the symptoms as data or facts as they are. The communication strategy carried out by the South Tapanuli BNNK in the Prevention, Eradication, Abuse and Illicit Trafficking of Drugs with various strategies including first, redudency (Repeat Communication Messages) so that it is remembered by the public. The second Bonding is strengthening the relationship between the South Tapanuli BNNK and people who have been involved with drugs and anti-drug volunteers formed by the South Tapanuli BNNK, the third is Bridging bridging the community who are cases or affected by drugs to the rehabilitation party for treatment to improve the affected people. The fourth linking builds connectivity to all elements that have an interest in eradicating P4GN.Keywords: Strategy, Comunication, P4GN